The Effect of Corporate Social Responsibility on Financial Performance and Shareholders Wealth - Akogo, Obehioye Usiomon; Ogbeide, Ivie Eloghosa (The Journal of Accounting and Management, 2025)
Objectives: The objective of the study is to examine the impact of corporate social responsibility (CSR) on financial performance and shareholders wealth. Particularly, return on assets, return on equity, shareholders earnings per share. Prior studies in developing countries such as Nigeria have conflicting findings and lack of understanding on the nature and extent of social information and its impact on firm performance. Approach: The study extracted secondary data from 5 Nigerian firms’ annual reports from 2018 to 2022. The data was analysed using tables and basic percentages and the statistical technique employed was General Least square (GLS) regression. Results: The study finds that CSR expenditure has a significant impact on financial performance and stock market price. Also, the study finds an insignificant impact between CSR and price earnings ratio and dividend payout ratio. Implications and Value: The paper emphasizes the significance of integrating CSR into business strategies for societal benefits and shareholder value creation, recommending that organizations incorporate CSR practices. The study also contributes to existing literature by examining the nature of social information and provides empirical evidence on the relationship between CSR and financial performance in developing countries, making it relevant for companies operating in these regions.